PENGARUH MOTIVASI, DISIPLIN, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN KOMISI PEMILIHAN UMUM KABUPATEN TAKALAR - Zulhajir Zulhajir; Syamsul Bahri; Andi Sugeng Sapta Aji (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
The good performance of the General Election Commission (KPU) employees in Takalar Regency will provide optimal contribution to the achievement of the implementation of the Presidential/Vice Presidential Election, the Election of Regional Heads at the Provincial and Regency Levels, and the Election of DPR/DPD Legislative Members at the Central/Regional Levels I and II. Therefore, as KPU employees, they are required to carry out their duties with full responsibility for the election implementation process. The purpose of this study is to determine (1) the influence of motivation on the performance of KPU employees (2) to determine the influence of discipline on the performance of KPU employees (3) to determine the influence of communication on the performance of KPU employees (4) to determine the influence of motivation, work discipline and communication together on the performance of KPU employees. The study used a quantitative method. The sampling technique used saturated sampling with 35 respondents. The data collection method was observation and questionnaires. The results of this study indicate that based on the results of the regression analysis there is a positive influence of the variables of motivation, discipline and communication on employee performance, both partially and simultaneously (together).